Experimental investigation of punching shear behaviour of ultra-high performance self-compacting concrete slabs - Mohamed A. El Zareef; Ayman G. Abdulrahaman; Ahmed Alnemari (Case Studies in Construction Materials, 2023)
The use of heavy reinforced and thick transfer-slab in multipurpose tall buildings is crucial to dealing with many issues such as high bending and punching shear stresses created from relocation of columns in floors above transfer-slab. Ultra-High Performance Self-Compacting Concrete (UHPSCC) is a proper option for coping with the problem of dense reinforcement. In predicting the punching shear capacity of concrete slabs, most existing code provisions limited the concrete compressive strength up to 70 MPa. Furthermore, no code provisions deal with estimating the punching shear capability of UHPSCC slabs. For these reasons, the present paper aims to investigate experimentally the punching shear behaviour of the interior slab-column joint made of a developed UHPSCC blend had a compressive strength of more than 120 MPa. The study takes into account the effect of design parameters such as type of concrete, slab thickness, and reinforcement ratio on the punching shear capacity. The study explores if the existing code shear provisions could be utilized to estimate the punching shear strength of UHPSCC and UHPC slab-column connections. In terms of estimating the punching shear capacity of such slab-column joints using available code provisions, regardless of their concrete compressive strength limits (using the available code formulae to estimate punching shear strength twice, once with the code restrictions of concrete compressive strength and once without), the available code shear models were significantly conservative, indicating the need to develop a new punching shear model for such slab-column connections. The European Code (EC2, 2004) has the best appropriate formula for predicting the nominal punching load capacity of UHSC slabs among the present well-known code punching provisions. The critical punching section of the UHPSCC slab was detected at 1.5 times the slab's effective depth measured from the column face. For a slab thickness of 200 mm, increasing the tensile steel ratio from 1.3% to 2.0% increased the punching strength of UHPSCC by 77.6%. At a reinforcement ratio of 1.7%, raising the slab thickness from 160 to 240 mm boosted the punching strength by 118.6%. In view of the study's outcomes, in addition to its ability to address the issue of dense reinforcement, the use of UHPSCC provides great potential for improving the punching shear capacity of heavy-loaded slab-column connections.